Collusion in a Bertrand duopoly model with decreasing returns and product differentiation - Contreras, Roberto (Estudios de Economía, 2016)
We study cartel stability in a differentiated price-setting duopoly with returnsto scale. We show that a cartel may be equally stable in the presence of lowerdifferentiation, provided that the decreasing returns parameter is high. In additionwe demonstrate that for a given factor of discount, there are technologiesthat can have decreasing returns to scale where the cartel always is stableindependent of the differentiation degree.